Does Size Matter? Genital Self-Image, Genital Size, Pornography Use and Openness Toward Cosmetic Genital Surgery in 3503 Swedish Men and Women. Issue 9 (16th July 2022) - Hustad, Ingvill Bagøien; Malmqvist, Karin; Ivanova, Ekaterina; Rück, Christian; Enander, Jesper
ABSTRACT: Background: Dissatisfaction with the appearance and size of one's genitalia is a common issue, and the use of cosmetic genital surgery is increasing among people with normal genitalia. Aim: This cross-sectional study aimed to investigate the distribution of genital self-image in a large sample of males and females, and whether selected factors could predict genital self-image. Methods: Three thousand five hundred three anonymous participants completed online questionnaires. Multiple linear regressions were used to identify the association between genital self-image and genital size (length of penis or protrusion of labia minora), consumption of sexually explicit material (SEM), sexual activity, avoidance and safety seeking behaviors, openness toward genital cosmetic surgery and age. Outcomes: Total scores on the Female and Male Genital Self Image Scale were used as the main outcome measures. Results: Overall, 3.6% of females and 5.5% of males had a severely low genital self-image (defined as 2 SD below the mean) and 33.8% of all individuals reported dissatisfaction with the appearance of their genitalia, with 13.7% of females and 11.3% of males considering undergoing cosmetic genital surgery. Mean protrusion of labia minora and stretched flaccid penis length in the population was estimated to 0.76 cm (95% CI 0.63–0.89 cm) and 12.5 cm (95% CI 12.33–12.76 cm), respectively. A higher genital self-image score was predicted by having a larger penis or less protruding labia minora, but not by the degree of SEM consumption, although 93.6% of males and 57.5% of females had consumed SEM in the past three months. The degree of avoidance and safety seeking behaviors, sexual activity, and openness toward genital cosmetic surgery predicted a low genital self-image. Being older was associated with a better genital self-image in females. Clinical Implications: The results show that a psychological intervention may be needed as an alternative to cosmetic genital surgery for people who are dissatisfied with the appearance of their genitals. Strengths and Limitations: This is one of few available studies investigating the association between actual genital size and genital dissatisfaction. The vast sample size and high response rate are also strengths. Limitations include the cross-sectional design, and possible bias in the study sample due to self-selection. Conclusion: Overall, a low genital self-image and dissatisfaction with one's genitalia is relatively common and is influenced not only by genital size, but also behaviors performed to alleviate worry about one's genitals.